The nationwide registry of hospitalized heart failure patients in Japan: Japanese Registry Of Acute Decompensated Heart Failure (JROADHF). (25th November 2020) - Ide, T; Kaku, H; Matsushima, S; Tohyama, T.I; Enzan, N; Funakoshi, K; Sumita, Y; Nakai, M; Nishimura, K; Fukuda, H; Hatano, M; Komuro, I; et al.
Abstract: Background and aim: Heart failure (HF) is a growing healthcare problem worldwide. This study aimed to describe clinical characteristics and long-term outcomes of HF patients in Japan. Methods and results: JROADHF (the Japanese Registry Of Acute Decompensated Heart Failure) is a retrospective, multicentre, nationwide observational database of 13, 238 patients hospitalized due to HF in 128 hospitals randomly selected from Japanese Circulation Society (JCS)-certified teaching hospitals during 2013. At inclusion, demographic and clinical data were collected from medical records with linkage to a nationwide claim-based database, the Japanese Diagnosis Procedure Combination (DPC). Patients were followed up to 5 years after discharge at each participating site. Patients were old as the median age of 81 years and women were older (74.8±12.8 vs 81.6±11.1 y.o). Mean left ventricular ejection fraction (LVEF) was 47%, and 45% were HF with preserved ejection fraction of >50% (HFpEF). Causes of HF included ischemic in 27%, valvular in 19%, arrhythmia in 17%, and hypertensive in 16%. Median length of hospital stay was 18 days and in-hospital mortality was 7.7%. All-cause mortality during 1 and 4 years were 22.3% and 48.4%, respectively. Hospitalization rates due to HF within 1 and 4 years were as high as 30.5 and 48.4%, respectively. Conclusions: Contemporary nationwide registry revealed that hospitalized HF patients were elder and had more HFpEF, and their prognosis was still poor compared to the data shown in prior registries. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Japan Agency for Medical Research and Development (AMED) Practical Research Project for Life-Style related Diseases including Cardiovascular Diseases and Diabetes Mellitus